Naturally Fermented Acid Slurry of Soy Whey: High-Throughput Sequencing-Based Characterization of Microbial Flora and Mechanism of Tofu Coagulation - Xu, Yunhe; Ye, Qing; Zhang, Huajiang; Yu, Yang; Li, Xiaona; Zhang, Zhen; Zhang, Lili (Frontiers in Microbiology, 2019)
Tofu processing generates large quantities of whey as waste water. Although naturally fermented whey serves as a coagulant, the critical constituents remain unknown. High-throughput sequencing identified predominant Lactobacillus in the naturally fermented acid slurry. Lactobacillus casei YQ336 with high coagulating ability and lactic acid production was isolated and its soy protein coagulating mechanism was determined. The acid in YQ336 fermented acid slurry lowered soy milk pH and reduced negatively charged groups of denatured soy protein, leading to coagulation. Acid slurry metal ions also promoted pH decline; moreover, YQ336-produced protease might partially hydrolyse soy protein, further promoting coagulation. Thus, organic acids, metal ions, and enzymes together promote coagulation, with the former acting as the main contributing factor. This study will pave the way for future industrial application of L. casei YQ336 in acid slurry tofu processing and food manufacturing, thereby potentially reducing resource waste and environmental pollution.